Legal Protection for Foreign Workers in Tourism Companies with Post-Divorce Individual Guarantees in Mixed Marriages in Indonesia - Desi Purnani; I Nyoman Putu Budiartha; Ni Luh Made Mahendrawati (Journal Equity of Law and Governance, 2023)
This research explores the impact of divorce in a mixed marriage on the work permit of Foreign Workers under individual guarantors in Indonesia. Although the work permit remains valid, divorce can reduce the legal protections and guarantees for foreign workers. Their basic rights should not be revoked, however, unresolved obligations and rights with the employing company should be noted. Companies are expected to assist foreign workers as guarantors for divorced ex-spouses, ensuring the completion of the remainder of their work permits. Government intervention is required to harmonize the relationship between companies and foreign workers through regulations governing the duration of work permits from issuance to expiration. Law No. 6 of 2023, passed by the legislature, confirms the state's commitment to protecting citizens' rights related to work and a humane life. This research utilizes the theories of legal protection, legal certainty, benefit, and justice with a juridical-normative and juridical-empirical/sociological approach. The findings highlight the gap between theory and practice, emphasizing the vacuum of norms in the application of the Job Creation Law Number 6 of 2023. The lack of justice, expediency, and legal certainty is related to the legal vacuum in the law.